2001
DOI: 10.1074/jbc.c100574200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Phospholipase C-ε by Heterotrimeric G Protein βγ-Subunits

Abstract: PLC-⑀ was identified recently as a phosphoinositidehydrolyzing phospholipase C (PLC) containing catalytic domains (X, Y, and C2) common to all PLC isozymes as well as unique CDC25-and Ras-associating domains. Novel regulation of this PLC isozyme by the Ras oncoprotein and ␣-subunits (G␣ 12 ) of heterotrimeric G proteins was illustrated. Sequence analyses of PLC-⑀ revealed previously unrecognized PH and EF-hand domains in the amino terminus. The known interaction of G␤␥ subunits with the PH domains of other pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
92
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 38 publications
6
92
0
Order By: Relevance
“…A constitutively activated form of Ga12, but not other Ga subunits, such as Gas and Gai, stimulated PLCe activity although the mechanism whereby the interaction between Ga12 and PLCe occurs remains totally unknown (Lopez et al, 2001). Moreover, Gbg enhanced PLCe activity when coexpressed in COS-7 cells presumably through the association of Gbg with a pleckstrin homology domain newly identified in PLCe (Wing et al, 2001). The effect of Gbg seems to be independent of the Ras pathways, implying that multiple regulatory signals converge at PLCe.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A constitutively activated form of Ga12, but not other Ga subunits, such as Gas and Gai, stimulated PLCe activity although the mechanism whereby the interaction between Ga12 and PLCe occurs remains totally unknown (Lopez et al, 2001). Moreover, Gbg enhanced PLCe activity when coexpressed in COS-7 cells presumably through the association of Gbg with a pleckstrin homology domain newly identified in PLCe (Wing et al, 2001). The effect of Gbg seems to be independent of the Ras pathways, implying that multiple regulatory signals converge at PLCe.…”
Section: Discussionmentioning
confidence: 98%
“…Although unidentified in initial studies, a pleckstrin homology domain and EF hands common to all PLC isozymes were recently reported to be found also in PLCe (Wing et al, 2001). However, their functions in the regulation of PLCe remain to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in substrate hydrolysis by PLCe in transfected cells have been observed after stimulation by diverse stimuli including epidermal growth factor (EGF), lysophosphatic acid (LPA), sphingosine-1-phosphate (S1P), adrenalin and acetycholine (Schmidt et al, 2001;Evellin et al, 2002;Kelley et al, 2004). Furthermore, these and other studies suggest that signaling pathways triggered by these agonists could be quite broad and in some cases independent of Ras family GTP-ases (Lopez et al, 2001;Wing et al, 2001Wing et al, , 2003Kelley et al, 2004). However, regarding that most approaches involved overexpression of PLCe, it still remains to be established which of the possible regulatory interactions are physiologically relevant.…”
Section: Introductionmentioning
confidence: 93%
“…PLCe, in common with other PI-PLC families, incorporates the PLC catalytic domain and C2 domain Lopez et al, 2001;Song et al, 2001); the presence of the PH domain and EF-hands has also been suggested (Wing et al, 2001). Within the unique regions, PLCe has CDC25 guanine exchange factor (CDC25 GEF) domain and two Ras-association or Rasbinding (RA/RBD) domains Lopez et al, 2001;Song et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Direct binding of H-Ras to the RA2 domain of PLC-⑀ results in increased accumulation of inositol phosphates in COS-7 cells co-expressing constitutively active H-Ras and PLC-⑀ (18). G␣ 12/13 , but not G␣ q or other heterotrimeric G␣ subunits (17,20), and G␤␥ subunits of heterotrimeric G-proteins (20) stimulate phospholipase activity of PLC-⑀; however, whether G␣ 12/13 and G␤␥ subunits activate PLC-⑀ via a direct interaction with the enzyme or through intermediate proteins remains unclear.…”
mentioning
confidence: 99%